Socio-Economic & Political Impact of COVID-19 - Mrs. Jayshree (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Education is not a mere process to comprehend the highest levels of knowledge but a continuous activity that creates new knowledge to sustain life across temporal and spatial barriers. Every society gives importance to education because it is a panacea for all evils. It is the key to solve the various problems of life. Education has been described as a process of waking up to life also. The development of effective education and its practices begin with proper education and training. Education is the catalyst which can effectively interlink all of them by bringing improvement in teaching-learning method and providing a good learning environment. Sudden spread of Pandemic i.e. COVID 19 has changed the whole scenario of educational environment. The traditional and innovative mode of teaching has changed and disruption has introduced in the educational sector. Online mode of education has become a need of the time. Use of automation in education has revolutionized the mode of education. In traditional teaching emphasis was given on human skills but COVID 19 has disrupted the education sectors and digital competency along with human skills have taken place in the educational sectors. Disruption in education will ask more from the side of teacher as it needs more honesty and commitment from the side of academic fraternity. Teachers are the spiritual guru and their approach and disruption in education will make it more effective and efficient in COVID era. Educators and higher education leaders must approach skills competency with a flexible growth mindset that will serve students well across the global, knowledge-based economy and throughout their careers. There is an undeniable need to train the next generation in emerging digital competencies and to be fluent in designing, developing or employing technology responsibly. This paper is based on secondary data and gave emphasis on the pros and cons of paradigm shift in education during COVID 19. Keywords:Education, Knowledge, Pandemic, Disruption, Skills